SMM DAN E-WOM DIMEDIASI TRUST TERHADAP PURCHASE INTENTION PADA PRODUK SUNSCREEN AZARINE - Maharani, Virgi; Budiarti, Anindhyta (JIEM : Journal Of International Entrepreneurship And Management, 2024)
This research aims to determine the influence of SMM or its abbreviation namely "Social Media Marketing" and E-WOM which for "Electronic Word of Mouth" towards Purchase Intention through Trust as the intervening variable. The research was quantitative. The data analysis technique used Partial Least Square (PLS) with SmartPLS 3.2.9 software. Furthermore, the data analysis technique used outer model, inner model, and hypothesis tests. The result concluded that social media marketing had a positive and significant effect on Trust. Likewise, electronic word of mouth had a positive and significant effect on Trust. Additionally, social media marketing had a negative and insignificant effect on Purchase Intention. Similarly, Both electronic word of mouth and Trust had a positive and significant effect on Purchase Intention. In addition, social media marketing had a positive and significant effect on Purchase Intention with Trust as an intervening variable. Likewise, electronic word of mouth had a positive and significant effect on Purchase Intention with Trust as an intervening variable. Abstrak: Penelitian ini mempunyai tujuan untuk mengetahui pengaruh yang dimiliki SMM ataupun kepanjangannya yaitu “Social Media Marketing” beserta E-WOM yang kepanjangannya yaitu “Electronic Word of Mouth” terhadap Purchase Intention melalui Trust sebagai variabel intervening. Jenis penelitian yang dipakai adalah penelitian kuantitatif. Metode analisis data yang dipakai yaitu PLS ataupun dikenal melalui “Partial Least Square” dengan memakai software SmartPLS 3.2.9. Teknik analisis data yang dipakai yakni outer model, inner model, serta uji hipotesis. Hasil penelitian memperlihatkan terkait SMM berpengaruh positif dan signifikan terhadap Trust, E-WOM berpengaruh positif dan signifikan terhadap Trust, SMM berpengaruh negatif dan tidak signifikan terhadap Purchase Intention, E-WOM berpengaruh positif dan signifikan terhadap Purchase Intention, Trust berpengaruh positif dan signifikan terhadap Purchase Intention, SMM berpengaruh positif dan signifikan terhadap Purchase Intention melalui Trust sebagai variabel intervening, serta E-WOM berpengaruh positif dan signifikan terhadap Purchase Intention melalui Trust sebagai variabel intervening.